2005
DOI: 10.2141/jpsa.42.308
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value of Khesari (Lathyrus sativus) for Growing and Laying Pullets

Abstract: The nutritional value of khesari (Lathyrus sativus), a grain legume, was determined for growing and laying pullets. Chemical analyses indicated khesari to be high in crude protein (,2-g/kg) and low in fat (+,.* g/kg) with estimated true metabolizable energy concentration of +,.* MJ/kg. Four hundred Shaver /13 brown pullets belonging to same source were randomly assigned to. dietary treatments with +** pullets each. Least-cost isocaloric and isonitrogenous diet containing raw khesari at *, +**, +/* or ,** g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…It is much lower than 12.5 MJ/kg DM, on average, reported for pea varieties (Smulikowska et al, 2001). It seems that the values 11.3 MJ ME/kg of L. sativus for poultry estimated by Latif et al (1976) and Hanbury et al (2000), as well as 12 MJ TME/kg estimated by Chowdhury et al (2005) might be too high.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It is much lower than 12.5 MJ/kg DM, on average, reported for pea varieties (Smulikowska et al, 2001). It seems that the values 11.3 MJ ME/kg of L. sativus for poultry estimated by Latif et al (1976) and Hanbury et al (2000), as well as 12 MJ TME/kg estimated by Chowdhury et al (2005) might be too high.…”
Section: Discussionmentioning
confidence: 63%
“…Grasspea (Lathyrus sativus L.), also known under other common names (fl at pea, everlasting pea, chickling pea, chickling vetch, khesari), is a very important source of protein grown as a pulse crop in some warm temperate and subtropical areas (Smartt et al, 1994;Chowdhury et al, 2005). It was already in use in Neolithic times and presently is considered a model crop for sustainable agriculture, as it may be grown on non-irrigated marginal land and is more resistant than other pulses to drought and fl oods, as well as to insect attack (Vaz Patto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that approximately 90 per cent of total feed cost is used to meet energy and protein requirements of poultry (FAO, ). Supplying the traditional energy and protein sources (maize, soya bean meal and fish meal) is costly in developing countries, and for this reason during the two last decades, there has been keen interest for finding and evaluating alternative local feed resources (Chowdhury et al., ; Trombetta et al., ; FAO, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhury et al. (), who studied the nutritional value of grass pea seed for growing and laying pullets, concluded that it may support growth performance of pullets either similar to or better than the control group. They reported that grass pea seed up to 150 g/kg diet was well tolerated for laying hens without any deleterious effects, and there were no symptoms of lathyrism in both grower and laying pullets.…”
Section: Introductionmentioning
confidence: 99%